Developing a roadmap for interventional oncology - Schönberg, Stefan; Attenberger, Ulrike; Solomon, Stephen B.; Weissleder, Ralph (The oncologist, 2018)
Interventional oncology uses image-guided procedures to enhance cancer care. Today, this specialty plays an increasingly critical role in cancer diagnosis (e.g., biopsy), cancer therapy (e.g., ablation or embolization), and cancer symptom palliation (e.g., nephrostomies or biliary drainages). Although the number of procedures and technical capabilities has improved over the last few years, challenges remain. In this article we discuss the need to advance existing procedures, develop new ones, and focus on several operational aspects that will dictate future interventional techniques to enhance cancer care, particularly by accelerating drug development and improving patient outcomes. Implications for Practice Interventional oncology is vital for cancer diagnosis, therapy, and symptom palliation. This report focuses on current interventional procedures and techniques with a look toward future improvements that will improve cancer care and patient outcomes.
Published Online First on June 29, 2018
Gesehen am 15.04.2020